Photocatalytical removal of inorganic and organic arsenic species from aqueous solution using zinc oxide semiconductor - Rivera-Reyna, Nidia (2013)
The photocatalytic removal of arsenite [As(III)] and monomethylarsonic acid [MMA(V)] was investigated in the presence of UV light (350 nm) and aqueous suspensions of ZnO synthesized by the sol–gel technique. Photocatalytic removal of these potent arsenic compounds results in the effective and rapid mineralization to less toxic inorganic arsenate [As(V)]. The effect of ZnO loading and solution pH on the treatment efficiency of the UV/ZnO photocatalytic process was evaluated. The optimal conditions for the removal of 5 mg L(−1) [As(III)] and [MMA(V)] aqueous solutions were observed at catalyst loadings of 0.25 and 0.50 g L(−1) with solution pH values of 7 and 8, respectively. Under these conditions, the activity of photocatalyst sol–gel ZnO was compared with TiO(2) Degussa P25 and commercial ZnO catalyst. The results demonstrate that the high adsorption capacity of ZnO synthesized by sol–gel gives enhanced removal of arsenic species from water samples, indicating that this catalyst is a promising material for treatment of arsenic contaminated groundwater.